The impact of behavioural structure of Romanian population on economic and social cohesion. - Dorel Ailenei; Amalia Cristescu; Coralia Angelescu (European Regional Science Association (ERSA), 2010)
The transition to market economy has represented both for Romania and other Central and Eastern European countries an emphasis on economic and social inequalities. The authors consider it is necessary to identify a path pass from chaotic inequalities to a state of economic and social cohesion that would allow to Romania recovery fast the gaps beside the developed E.U. countries. To identify the behavioural structure of Romanian population we designed a national survey. Once identified this structure we can determine the contribution of behavioural types to the economic and social cohesion state and we can estimate the possibilities of change in the medium-term of behavioural structure according with economic and social changes caused by the transition to a market economy. For this, we will correlate the levels of satisfaction of human needs from Maslow's Pyramid with the degrees of participation in economic and social life by means of fuzzy implication functions. Thus, we can achieve a better highlighting of the economic and social cohesion factors at national and regional level, and on this basis we can obtain a profile of national and regional cohesion state. The authors consider that the success of Romania's E.U. integration depends primarily on the behavioural profile of the population. The question arises is: E.U. integrates a "cohesive zone" or integrates behavioural types in relation to the standards of the European citizen.
Keywords: R10; Z13; 330; behavioural structure; fuzzy sets; regional profile of economic; social cohesion